Flight to Safety: COVID-Induced Changes in the Intensity of Status Quo Preference and Voting Behavior: A Comment on Bisbee and Honig - Alice Malmberg; Daniel Scates (Institute for Replication (I4R), 2023)
Bisbee and Honig (2022) examine the effect of the COVID-19 pandemic on voting for Bernie Sanders in the 2020 Democratic Party primary using a difference-in-differences design, finding evidence that exposure to COVID-19 resulted in a 7-15 percentage point increase in voting for Biden. The study also uses a regression design with district-level fixed effects to estimate the effect of the COVID-19 pandemic on voting for anti-establishment candidates during the US 2020 House primaries. It finds evidence that an increase in COVID cases was associated with a decline in voting for anti-establishment candidates in general, and for those endorsed by the Tea Party. We re-run the code for all tests in this paper, successfully reproducing its results in a preliminary replication. We then use the De Chaisemartin and D'Haultfoeuille difference-in-differences estimator to replicate their main results, finding that though the coefficient remains negative, the results are not statistically significant. We also replicate their tests regarding US House primary candidates using a different measure of anti-establishment candidates. Here, we find that the interaction term between anti-establishment candidates and COVID-19 remain statistically significant, with the same sign. Finally, we employ an expanded dataset that includes Congressional primary candidates that were omitted in the initial dataset, as well as a re-coded extremism variable that also includes candidates endorsed by Donald Trump. These updated findings corroborate the paper's initial results. However, due to a restrictive number of observations that interfered with our application of the De Chaisemartin and D'Haultfoeuille estimator, we believe that the expanded U.S. House primary results constitute the more robust half of our replication.
Keywords: 330